Extracellular vesicle-based therapeutics: natural versus engineered targeting and trafficking - Murphy, DE; de Jong, OG; Brouwer, M; Wood, MJ; Lavieu, G; Schiffelers, RM; Vader, P (Springer Nature, 2019)
Extracellular vesicles (EVs) are increasingly being recognized as mediators of intercellular signaling via the delivery of effector molecules. Interestingly, certain types of EVs are also capable of inducing therapeutic responses. For these reasons, the therapeutic potential of EVs is a topic of intense research, both in the context of drug delivery and regenerative medicine. However, to fully utilize EVs for therapeutic purposes, an improved understanding of the mechanisms by which they function would be highly advantageous. Here, the current state of knowledge regarding the cellular uptake and trafficking of EVs is reviewed, along with a consideration of how these pathways potentially influence the functions of therapeutic EVs. Furthermore, the natural cell-targeting abilities, biodistribution profiles, and pharmacokinetics of exogenously administered EVs, along with the components responsible for these features are discussed. An overview of the potential clinical applications and preclinical examples of their successful use is also provided. Finally, examples of EV modifications that have successfully been employed to improve their therapeutic characteristics receive a particular focus. We suggest that, in addition to investigation of EV cell targeting and routes of uptake, future research into the routes of intracellular trafficking in recipient cells is required to optimally utilize EVs for therapeutic purposes.